2009
DOI: 10.1103/physreva.79.020103
|View full text |Cite
|
Sign up to set email alerts
|

Gamma flashes from relativistic electron-positron plasma droplets

Abstract: Ultra-intense lasers are expected to produce, in near future, relativistic electron-positron plasma droplets. Considering the local photon production rate in complete leading order in quantum electrodynamics (QED), we point out that these droplets are interesting sources of gamma ray flashes. . Electron-positron plasmas are also interesting for astrophysical scenario [10]. Temperatures of about T ∼ 10 MeV, in a laser-generated plasma, would open, furthermore, channels for muon or pion production [11]. While th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…This offers prospects for laboratory studies on relativistic e + e − plasmas which are of relevance to various astrophysical phenomena such as gamma-ray bursts, supernova explosions, and the evolution of the early universe [9]. Meanwhile, theoreticians have started to explore (ultra-) relativistic e + e − plasmas with densities 10 30 cm −3 , analyzing the thermalization process [10], dynamical properties [11], and photo-emission spectra [12]. In particular it was shown that in these extremely dense environments higher-order QED processes and multi-particle correlation effects may be prominent.…”
mentioning
confidence: 99%
“…This offers prospects for laboratory studies on relativistic e + e − plasmas which are of relevance to various astrophysical phenomena such as gamma-ray bursts, supernova explosions, and the evolution of the early universe [9]. Meanwhile, theoreticians have started to explore (ultra-) relativistic e + e − plasmas with densities 10 30 cm −3 , analyzing the thermalization process [10], dynamical properties [11], and photo-emission spectra [12]. In particular it was shown that in these extremely dense environments higher-order QED processes and multi-particle correlation effects may be prominent.…”
mentioning
confidence: 99%
“…We consider kinetic evolution of nonequilibrium optically thick plasma consisting at the moment t = 0 of electron-positron pairs with number density n = 10 30 cm −3 in the small region with radius R 0 = 200 cm and average particle energy 600 keV. Although such parameters are far from both laboratory conditions and the real GRB sources, we consider this choice of parameters important since it provides some new insights with respect to the traditional hydrodynamic description 15,33,34,13,35 . Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Electron-positron plasmas in the laboratory experiments or in thunderstorms have low density and are consequently optically thin 13,14 . In contrast, in a GRB source pair plasma is dense and optically thick 4,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The Ps atom thereby becomes a 'microcollider' in which laser-driven e − + e + collisions occur at small impact parameters; e.g., an infrared laser with wavelength λ = 1 mm, and intensity I = 5.5 × 10 22 W/cm 2 can provide the threshold energy to create a muon + antimuon pair [4,5]. Other ambitious prospects, fostered by attaining high densities, include Bose-Einstein condensation of Ps in pursuit of an annihilation gamma ray laser [6].…”
Section: Introductionmentioning
confidence: 99%